The metabolism of L-arginine and its significance for the biosynthesis of endothelium-derived relaxing factor: L-glutamine inhibits the generation of L-arginine by cultured endothelial cells. - Sessa, W C (1990)
The mechanism by which L-glutamine (L-Gln) inhibits the release of endothelium-derived relaxing factor from bovine aortic cultured endothelial cells was investigated. The intracellular concentration of L-arginine (L-Arg) in Arg-depleted endothelial cells was inversely related to the level of L-Gln. Removal of L-Gln from the culture medium (usually containing L-Gln at 2 mM) abolished the inhibitory effect of the culture medium on L-Arg generation. L-Gln (0.2 and 2 mM) but not D-Gln inhibited the generation of L-Arg by both Arg-depleted and nondepleted endothelial cells. L-Gln did not interfere with the uptake of L-Arg or the metabolism of L-Arg-L-Phe to L-Arg but inhibited the formation of L-Arg from L-citrulline (L-Cit), L-Cit-L-Phe, and NG-monomethyl-L-arginine. L-Gln also inhibited the conversion of L-[14C]Cit to L-[14C]Arg by Arg-depleted endothelial cells. However, L-Gln did not inhibit the conversion of L-argininosuccinic acid to L-Arg by endothelial cell homogenates. Thus, L-Gln interferes with the conversion of L-Cit to L-Arg probably by acting on argininosuccinate synthetase rather than argininosuccinate lyase. L-Gln also inhibited the generation of L-Arg by the monocyte-macrophage cell line J774 but had no effect on the conversion of L-Cit to L-Arg by these cells. As the release of endothelium-derived relaxing factor from cultured and non-cultured endothelial cells is limited by the availability of L-Arg, endogenous L-Gln may play a regulatory role in the biosynthesis of endothelium-derived relaxing factor.